A Review on Green Synthesis, Antimicrobial Applications and Toxicity of Silver Nanoparticles Mediated by Plant Extract - Subakir Salnus; Wahid Wahab; Rugaiyah Arfah; Firdaus Zenta; Hasnah Natsir; Muriyati Muriyati; Fatimah Fatimah; Arini Rajab; Zulfian Armah; Rizal Irfandi (Indonesian Journal of Chemistry, 2022)
Nanotechnology explores nanoscale materials that can be used in a wide range of industries such as biotechnology, cosmetics, drug delivery, nanomedicine, and biosensors. Nanoparticles in diverse shapes and sizes can be prepared through physical, chemical, and biological methods. The employment of reducing agents, which will change their form, size range, level of stability, and interaction, is a crucial part thus employing a biological approach is necessary. Chemically generated metal oxide nanoparticles raise considerable issues owing to the usage of hazardous and poisonous chemicals, as well as the potential for conservational impairment. In contrast, the production of silver nanoparticles using the principal method of green synthesis has found a special place in research that is considered more environmentally approachable requiring the use to produce non-toxic nanomaterials. Plants and polymer materials have received a lot of interest in the preparation of nanoparticles since they are renewable and affordable. In this review, we present a comprehensive overview of more ecologically friendly synthesis techniques that use plant extracts to make silver nanoparticles and their application as antibacterial agents, as well as toxicity features based on the shape, size range, and phytochemical mechanism of plants.